Personal Resources of the Professional’s Stress Tolerance - Medvedeva, Tatyana Y. (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Purpose: The investigation is dedicated to the study of personal resources of stress tolerance in work activities by the example of the medical workers. Materials and Methods: As a resource of stress negotiation in complex professional situations happened with the specialists of different age groups, we consider person vitality as a complex structured psychological formation, system of persuasions which contribute to the development of readiness to manage the situation of increased complexity and system of life guidance. Results: These inside criteria are important for the life prosperity, process orientation, result of activity, and feeling of being an origin of professional development. We analyzed coping strategies for the control of professional situations, used in the professional activity. During the experimental research, we identified the specific character of doctors’ stress tolerance, concerned with a high professional motivation, self-confidence as a professional, which can prevent the professional burnout. Along with this fact, high activities of depersonalization in combination with non-productive coping strategies reveal the problems with patients’ interaction. During the investigation, we revealed that the respondents (medical workers of children’s polyclinic) have both the high activities of managerial stress receptivity and the high activities of vitality, caused by drawing in labor activity and feeling of control under what is going on at present, ability to risk in professional situations. Conclusion: The revealed connection of personal characteristics and components of stress tolerance display that they can be as a resource of stress tolerance.